Day-Length Is Involved in Flooding Tolerance Response in Wild Type and Variant Genotypes of Rootstock Prunus cerasifera L. - Iacona, Calogero; Pistelli, Laura; Cirilli, Marco; Gatti, Lorenzo; Mancinelli, Roberto; Ripa, Maria Nicolina; Muleo, Rosario (Frontiers in Plant Science, 2019)
Scenarios for current and predicted climate changes require crops with an improved adaptability to mutable environmental features. A condition of hypoxia in the roots activates coping mechanisms to develop strategies to overcome the reduction of oxygen. Prunus spp are hypoxia-sensitive woody species and although much information has been accumulated in the last decades, many physiological mechanisms are still unclear. To verify whether anoxic plant responses are also regulated by photoperiod, plants of Mr.S.2/5-WT plum, and its variant genotypes S.4 tolerant (plus) and S.1 sensitive (minus) to flooding, were grown in greenhouse and were submitted from mid-July to natural (NP) and to constant photoperiod (CP) until the first ten-days of October. From mid-September plants from each genotype, grown under the two photoperiods, were divided into two groups applying long-term flooding only to one of them. Gas exchange parameters, energetic and biochemical activities, leaf chlorophyll contents, and stress symptoms were measured at different times, whereas soluble sugars were quantified in leaves and roots 14 days after flooding, when stress symptoms in WT and S.1 became prominent. Seasonal changes in photoperiod played a role in the adaptability to anoxia, although flooding stress response differed among the three genotypes. Anoxia affected leaf gas exchange and S.4 flooded-leaves retained higher ACO2 under conditions of NP and CP. Leaf soluble sugar concentration differed among genotypes. Irrespective of photoperiod, S.4 anoxic-leaf sugar concentration was the lowest, except for sorbitol. S.4 anoxic-roots under CP accumulated the highest levels of sucrose and sorbitol. An influence by the photoperiod was observed in WT and S.1 anoxic-leaves, whereas, irrespective of photoperiod, S.1 anoxic roots accumulated the lowest concentration of sugars. Leaf and root respiratory activity in flooded-plants was highest in S4, and ADH activity increased in all flooded plants under CP, but a higher activity was observed only in S.1 under NP during flooding. Results are consistent with the hypothesis that the S.4 genotype has a plastic adaptability to flooding stress, escaping from the photoperiod regulatory cross-talk system, and can better cope with the new scenarios generated by climate changes.